Integrated current-sensing circuit with offset-current cancellation for DC-DC boost converters using 0.13µm CMOS technology / Intan Shazana Shamsul Sahar and Tuan Norjihan Tuan Yaakub - Shamsul Sahar, Intan Shazana; Tuan Yaakub, Tuan Norjihan (UiTM Press, 2014)
The project proposed a configuration of CMOS current sensing circuit with offset-current cancellation for boost converters. This design will contrast the power and operational sensing speed with the traditional proposed current-sensing circuit. By eliminating the offset-current, it will improve the current sensing performance. It can be accomplish by applying current mirror as opposed of utilizing operational amplifier as a voltage follower in conventional design which serves to subside power consumption due to reducing the number of transistor. Moreover, this proposed design also can cancel off the offsetcurrent in the traditional current sensing circuit, thus the improvement of sensing-accuracy will accomplished. The proposed design will be designed using 0.13µm technology and simulation will be carried out in Mentor graphics. The dc-dc boost converter will be set with operating frequency of 500kHz and designed with the supply voltage of 2V.